Digital technologies and healthcare architects' wellbeing in the National Health Service Estate of England during the pandemic - Chrysikou, Evangelia; Papadonikolaki, Eleni; Savvopoulou, Eleftheria; Tsiantou, Eleni; Klinke, Christian Alexander (Frontiers in Medical Technology, 2023)
Introduction UK Built Environment is currently undergoing a digital transformation, as is happening in the National Health Service (NHS) of England. In this paper, the focus was on the intersection of the two sectors and specifically the potential digital transformation of the NHS Estate. The NHS has developed a strategy for its workforce, to improve staff health and wellbeing, and support equality, diversity, inclusion and the development of existing staff. Digital technologies (DTs) can relate to all Estates and Facilities Management priorities, as it cross-cuts all proposed actions. As opposed to most studies on the wellbeing of blue-collar workers, this article focuses on white-collar workers, specifically architects working in the NHS, especially since NHS at this stage is developing two important policies: the New Hospital Programme and the Workforce Action Plan. Therefore, it is important for the NHS to look at the digital transformation strategy in the prism of the other two. As architecture traditionally has low job satisfaction, it negatively impacts wellbeing. This study argues that this might have been accentuated during the pandemic for the architects working in the NHS and dealing with the added pressure from three new major tasks: adjusting the infrastructure capacity to fight Covid-19; and creating the infrastructure for the testing and vaccination programs. DTs in architecture potentially affect job satisfaction in terms of creativity, autonomy, time pressure, organisational commitment, and so on. Methodology The methodology comprises a literature review and a pilot of interviews with healthcare architects/designers working in the NHS or on NHS-related projects. The research context is informed by the COVID-19 crisis that brought healthcare architecture to the frontline of the pandemic, with NHS architects creating new wards and vaccination centers, while private healthcare architects designed new hospitals. Results In the niche area of healthcare architecture, architects were in their busiest year. Yet, the DTs available to them then could only support limited tasks and did not link well to operational data. Discussion To explore how DTs transform the wellbeing of healthcare architects, understanding wellbeing in healthcare architecture in light of digital transformation is crucial for creating the necessary leadership for the sector to grow.